O10.3. EXPOSURE TO COMMON INFECTIOUS PATHOGENS IN SUBJECTS AT CLINICAL HIGH RISK FOR PSYCHOSIS: CLINICAL AND IMMUNOBIOLOGICAL ASSOCIATIONS. (9th April 2019) - Pollak, Thomas; Kempton, Matthew; Iyegbe, Conrad; Cotter, David; Föcking, Melanie; Cagney, Gerard; Valmaggia, Lucia; Stone, James; Vincent, Angela; Yolken, Robert H; David, Anthony; McGuire, Philip; et al.
Abstract: Background: Exposure to infectious microorganisms has been implicated as an important risk factor in the development of psychotic disorders. Epidemiological and laboratory evidence suggests that exposure at various developmental periods may increase psychosis risk, from in utero through to childhood and adult life. Individuals who meet clinical high risk (CHR) criteria are at substantially increased risk of developing a psychotic disorder; however, no study to date has explored whether exposure to schizophrenia-associated pathogens is associated with clinical outcomes in this population. Methods: Plasma samples from 254 subjects at ultra-high risk of psychosis from the EU-GEI cohort and 116 age- and sex-matched controls were tested for antibodies to the following infectious organisms: Toxoplasma gondii, herpes simplex virus type 1, cytomegalovirus, Epstein-Barr virus (EBV) and influenza. Samples were also tested for antibodies to the NMDA receptor using a fixed cell-based assay and for levels of S100B (a putative marker of blood-brain barrier disruption) and complement pathway protein expression. Only pathogens which predicted case-control status were taken through to further analysis looking at symptomatic associations and clinical outcome measures, which included the Positive and Negative Symptom Scale (PANSS), the Scale for Assessment of Negative Symptoms (SANS) and Global Assessment of Function (GAF). Results: In logistic regression analysis, exposure to Toxoplasma was associated with increased risk of meeting CHR criteria (OR 2.66; p = 0.04), whereas EBV exposure was associated with decreased risk of meeting CHR criteria (OR 0.34; p = 0.006). Toxoplasma IgG antibody status was associated with higher SANS scores (p = 0.032) and higher GAF symptoms (p = 0.003) and disability scores (p = 0.003). EBV antibody status was associated with lower GAF scores (p = 0.007), indicating better functioning. In clinical outcome analysis, EBV antibody positivity was associated with a reduced risk of transition to psychosis (OR 0.44; p = 0.04), whereas Toxoplasma IgG seropositivity was associated with poorer functional outcomes at follow-up. The presence of NMDAR autoantibodies was associated with higher Toxoplasma IgM (p = 0.024), but not IgG (p = 0.972), titres. Furthermore, Toxoplasma IgM was associated with increased levels of serum S100B (p = 0.007) and with increased expression of Complement C4 (p = 0.018, FDR corrected), both of which have been independently implicated in psychosis risk. Discussion: Toxoplasma exposure is associated with severity of negative symptoms and poor functional outcomes in CHR individuals, consistent with the known associations of Toxoplasma exposure in psychotic patients. Specific mechanisms by which Toxoplasma exposure might confer risk of poor outcomes include activation of specific complement pathway proteins, disruption of the blood-brain barrier and infection-induced production of brain-reactive autoantibodies. EBV exposure appears to have a mitigating effect, symptomatically and in terms of outcome, in this population, and as such may represent one of the first reported neurobiological protective factors for the CHR state and for the subsequent development of psychosis.